Between a Rock and a Hard Place: Adventures in Treating Calcific Femoropopliteal Disease. Issue 6 (May 2017) - Heuser, Richard
Key Points: SFA disease has unique challenges A myriad of interventional techniques have been proposed to treat calcific femoral disease It appears a combination of atherectomy and drug elution may be the procedure of choice in these patients New innovative therapies may be a viable option in the future